2020
DOI: 10.1002/advs.201903318
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Thermal‐Budget Doping of 2D Materials in Ambient Air Exemplified by Synthesis of Boron‐Doped Reduced Graphene Oxide

Abstract: Graphene oxide (GO) doping and reduction allow for physicochemical property modification to suit practical application needs. Herein, the challenge of simultaneous low‐thermal‐budget heteroatom doping of GO and its reduction in ambient air is addressed through the synthesis of B‐doped reduced GO (B@rGO) by flash irradiation of boric acid loaded onto a GO support with intense pulsed light (IPL). The effects of light power and number of shots on the in‐depth sequential doping and reduction mechanisms are investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…Notably, the heating rates and maximum temperatures varied as a function of the type of dopant as well as their concentration. Specifically, we hypothesize that the elevated temperatures (>1000 °C) induced in the host materials by momentary photothermal treatment provide a sufficient driving force for the release of oxygen atoms from the oxide lattice due to the formation of an oxygen concentration gradient across the interface between the oxide lattice and ambient air, serving as a quasi-reducing environment in the high-temperature transient. ,, As a result, the IPL-treated samples would undergo a partial reduction of the oxide lattice near the surface for the formation of several WO 3– x /WO 3 heterojunctions while also forming exsolved metal NPs, together with facilitating a higher catalytic activity and chemiresistive sensitivity. By controlling the IPL irradiation conditions, such as the number of shots and duration of irradiation times, the size and distribution of NPs could be adjusted for optimizing the catalytic behavior for various applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the heating rates and maximum temperatures varied as a function of the type of dopant as well as their concentration. Specifically, we hypothesize that the elevated temperatures (>1000 °C) induced in the host materials by momentary photothermal treatment provide a sufficient driving force for the release of oxygen atoms from the oxide lattice due to the formation of an oxygen concentration gradient across the interface between the oxide lattice and ambient air, serving as a quasi-reducing environment in the high-temperature transient. ,, As a result, the IPL-treated samples would undergo a partial reduction of the oxide lattice near the surface for the formation of several WO 3– x /WO 3 heterojunctions while also forming exsolved metal NPs, together with facilitating a higher catalytic activity and chemiresistive sensitivity. By controlling the IPL irradiation conditions, such as the number of shots and duration of irradiation times, the size and distribution of NPs could be adjusted for optimizing the catalytic behavior for various applications.…”
Section: Resultsmentioning
confidence: 99%
“…Then, by applying IPL irradiation, sub-10 nm metal NPs were formed on the surface of WO 3 NFs with a uniform distribution (IPL_exsolved M-WO 3 NFs), indicative of the exsolution of the noble metal species from the oxide matrix. The IPL irradiation method induces little to no phase transition in the host oxides owing to its ultrafast processing time (<20 ms) . In addition, we investigated the practical feasibility of the IPL-generated exsolved NP catalysts by evaluating the chemiresistive gas sensing performances of IPL_exsolved M-WO 3 NFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both technologies necessitate delicate regulation of processing time and applied power: insufficient energy would lead to a product with low carbon content and short-chain polymeric debris, while excess energy could destroy the porous structure of wood. While more simple and ultrafast pyrolysis methods on the basis of carbothermal shock or intense pulsed light (processing times of less than 1 s) , have been reported in recent works, they are in an early developmental stage with limited lab-scale capabilities despite their large potential. On the other hand, recycling the waste thermal energy produced from the carbonization process can be a sustainable way to conserve energy and cost, which should be considered in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…106 Graphene oxide (GO) or its reduced form, reduced graphene oxide (rGO) are two graphene derivatives that can be exfoliated from graphite using the Hummers method. GO and rGO surface functional groups, including hydroxyl, carboxyl, and epoxy groups, are sensitive to tactile stimuli, such as pressure 107,108 and strain, 109,110 as well as environmental factors, such as humidity, 111,112 chemicals, 113,114 and temperature. 115,116 Cho et al 117 reported a transparent and stretchable allgraphene multifunctional e-skin sensor matrix that used chemical vapor deposition-grown graphene to form the electrodes and interconnects for these three sensors, and used GO and rGO as the active sensing materials for humidity and temperature sensors, respectively (Figure 4A).…”
Section: D Nanomaterialsmentioning
confidence: 99%